Burnout among Gynaecological and Obstetrical Resident Doctors in Tertiary Health Care Settings of Pakistan - Eyan Khan, Muhammad; E Yazdaan, Hamd; ullah, Naeem; Imran Marwat, Muhammad; Khan, Khushal; Mohammad Omair, Syed (ADVANCES IN BASIC MEDICAL SCIENCES, 2023)
Objective To assess the prevalence and degree of burnout among resident doctors of gynaecological and obstetrical units in tertiary care hospitals of district. Methodology A cross sectional study was implied by using Maslach Burnout Inventory questionnaire as a validated study tool to analyse the 3 dimensions of burnout. Data was collected from resident doctors of various category tertiary care hospitals including public, private and autonomous hospitals in district Peshawar. Non-probability convenience type of sampling technique was used and the residents were selected irrespective of gender or age. Three levels of burnout dimensions were calculated and comparison was made among residents of different category hospitals. Results Of the 212 distributed self-administered questionnaires, 147 were returned (69% response rate). Highest prevalence of high burnout levels were recorded among the study participants in Emotional Exhaustion component with 62 percent followed by 39 percent in Depersonalization and 26 percent in reduced personal accomplishment. Autonomous public hospitals recorded the highest levels of emotional exhaustion and depersonalization whereas reduced personal accomplishments levels were the highest among residents in public hospitals. Conclusion Results revealed high burnout with high levels of emotional exhaustion in all hospitals. Similarly high levels of reduced personal accomplishment had the lowest prevalence. Proper patient referral system and greater number of doctor (in order to improve the doctor patient ratio) are needed in order for adequate patient load distribution. Screening programs for early detection, interventions and proper stress management programs to better cope with the hectic routine. Key words: Burnout syndrome, emotional exhaustion, depersonalization, reduced personal accomplishment, resident doctors